Pendidikan Anak Usia Dini di Indonesia: Permasalahan Kurikulum Taman Kanak Kanak - Yulianti Dwi Astuti (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2004)
The early childhood years are important because in this period all developmental aspects (physical, emotional, and intellectual) grow at their fullest pace. Unfortunately, parents, society and government (through their school system) in Indonesia show a lack of awareness on the importance of giving early stimulation (formal and also non formal) to children at this age. As a result, treatment to children, in their learning and growing process, tend to be developmentally inappropriate. The current paper tries to examine the problem of giving developmentally appropriate learning environment in kindergarten. The length of the school is only one dimension of the kindergarten experience. Other important issues include the nature of the kindergarten curriculum and the quality of teaching. Changing the length of the hours spent in kindergarten is not as important as making sure that all kindergarteners are provided with developmentally and individually appropriate learning environment. Developmentally appropriate kindergarten classroom must have one thing in common: the focus will be on the development of the child as a whole.Keywords: early childhood, kindergarten curriculum